2012
DOI: 10.1155/2012/302495
|View full text |Cite
|
Sign up to set email alerts
|

PPARα-Independent Arterial Smooth Muscle Relaxant Effects of PPARαAgonists

Abstract: We sought to determine direct vascular effects of peroxisome proliferator-activated receptor alpha (PPARα) agonists using isolated mouse aortas and middle cerebral arteries (MCAs). The PPARα agonists GW7647, WY14643, and gemfibrozil acutely relaxed aortas held under isometric tension and dilated pressurized MCAs with the following order of potency: GW7647≫WY14643>gemfibrozil. Responses were endothelium-independent, and the use of PPARα deficient mice demonstrated that responses were also PPARα-independent. Pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 55 publications
1
5
0
Order By: Relevance
“…In support of a nongenomic effects, a study has shown that PPAR agonists of various chemical structures rapidly diminished ERK phosphorylation in human microvascular endothelial cells in parallel to their known receptor binding affinity [178]. Similarly, our recent findings showing a fast, PPAR -mediated, enhanced cardiac muscle contractility and blood vessel relaxation is in support of the existence of such nongenomic receptor pathways [179]. Furthermore, a most recent study has demonstrated that pioglitazone, a PPAR agonist, rapidly reduced neuropathic pain through non-genomic PPAR mechanisms [180].…”
Section: Nongenomic Pathways To Ppar Effectssupporting
confidence: 80%
“…In support of a nongenomic effects, a study has shown that PPAR agonists of various chemical structures rapidly diminished ERK phosphorylation in human microvascular endothelial cells in parallel to their known receptor binding affinity [178]. Similarly, our recent findings showing a fast, PPAR -mediated, enhanced cardiac muscle contractility and blood vessel relaxation is in support of the existence of such nongenomic receptor pathways [179]. Furthermore, a most recent study has demonstrated that pioglitazone, a PPAR agonist, rapidly reduced neuropathic pain through non-genomic PPAR mechanisms [180].…”
Section: Nongenomic Pathways To Ppar Effectssupporting
confidence: 80%
“…Segments 3-4 mm in length were mounted on pins in chambers of a DMT 610M wire myograph system (Danish Myo Technology, Aarhus N, Denmark) containing Krebs buffer (in mM: 119 NaCl, 4.7 KCl, 0.24 NaHCO 3, 1.18 KH 2PO4, 1.19 MgSO4, 5.5 glucose, and 1.6 CaCl2) saturated at 37°C with a gas mixture containing 20% O 2-5% CO2-75% N2 (Airgas Mid-South, Tulsa, OK) at 37°C. Arterial rings were progressively stretched to 0.75 g equivalent force passive tension in 0.1 g steps and allowed to equilibrate for 45 min as described previously (58,59). Force changes were recorded using an ADinstruments (Colorado Springs, CO) PowerLab 4/30 and associated LabChart Pro software (v. 6.1) running on a standard Windows XP computer platform.…”
Section: Methodsmentioning
confidence: 99%
“…In isolated mouse aortas and middle cerebral arteries, the tension of middle cerebral arteries was inhibited by GW7647, WY14643 and gemfibrozil. But it was negative in PPARα‐deficient mice, demonstrating that actions were PPARα‐independent . In mice treated with a PPARα activator, the smooth muscle cell proliferation, tissue factor expression and neointimal formation were observed only in Ppara‐ null mice .…”
Section: Discussionmentioning
confidence: 99%
“…But it was negative in PPARadeficient mice, demonstrating that actions were PPARaindependent. [46] In mice treated with a PPARa activator, the smooth muscle cell proliferation, tissue factor expression and neointimal formation were observed only in Ppara-null mice. [47] In this study, MS symptoms developed in Pparanull mice and they were inhibited by low dose of gemfibrozil and fenofibrate, respectively.…”
Section: Figurementioning
confidence: 98%